Catheter-based left atrial appendage CLOSURE in patients with atrial fibrillation at high risk of stroke and bleeding as compared to best medical therapy: rationale and design of the prospective randomized CLOSURE-AF trial - Landmesser, Ulf; Skurk, Carsten; Kirchhof, Paulus; Lewalter, Thorsten; Hartung, Johannes; Rroku, Andi; Pieske, Burkert; Brachmann, Johannes; Akın, Ibrahim; Jacobshagen, Claudius; Meder, Benjamin; Zeiher, Andreas M.; et al. (American heart journal, 2026)
Background - Percutaneous catheter‐based left atrial appendage (LAA) closure is a potential alternative to oral anticoagulation for stroke prevention in patients with atrial fibrillation (AF). The effectiveness and safety of LAA closure in patients with AF at high risk of stroke (CHA2DS2‐VASc Score ≥2) and high risk of bleeding compared to best medical care including a nonvitamin K antagonist oral anticoagulant [NOAC] when considered eligible is not known. - Methods/Design - The prospective, multicenter, randomized clinical Left atrial appendage CLOSURE in patients with Atrial Fibrillation at high risk of stroke and bleeding compared to medical therapy (CLOSURE-AF) trial compared catheter-based LAA closure to best medical care (including NOAC therapy if considered eligible) in patients with AF at high risk of stroke and with either a history of bleeding or a high estimated bleeding risk (HASBLED ≥ 3). The primary endpoint is time to a composite of first stroke (ischemic or hemorrhagic), systemic embolism, cardiovascular or unexplained death or major bleeding (Bleeding Academic Research Consortium 3-5). Secondary outcomes include components of the primary outcome and total mortality. The primary efficacy analysis will be performed in the intention‐to‐treat population using Cox regression models for noninferiority with an option to test for superiority once noninferiority has been proven. - Results - The first patient in the CLOSURE-AF trial was enrolled in March 2018. By April 2025 the complete study cohort of n = 912 patients had been enrolled in 42 sites. - Conclusion - CLOSURE-AF will contribute evidence on the effectiveness and safety of LAA occlusion compared to optimal medical therapy in patients with AF at high risk of stroke and bleeding. The trial results will help to define the clinical use of catheter-based LAA closure in the future. - Trial Registration - clinicaltrials.gov Identifier: NCT03463317